Los foraminíferos de la formación umir (sección quebrada la julia): registro del cretácico superior cuspidal (maastrichtiano) en el valle medio del magdalena, colombia (1995)
A very prolific association of foraminifera, represented by 17 different species between benthonic and planktonic forms, has been identificed by a detailed analysis of the Umir Formation (La Julia Creek Section, Middle Magdalena Valley). The presence of Ammobaculites colombianus Cushman and Hedberg with Rugoglobigerina macrocephala Brönnimann in the lower part of the sedimentary sequence, Umir Formation, is reported for the first time. This finding allows to assign a Maastrichtian age to this unit (at least to the lower part) instead of Campanian-Maastrichtian as It had been previously attempted. Lack of foraminifera with stratigraphical value in the upper part of the sedimentary sequence did not allow to identify the presence of the latest Maastrichtian and the lower most Paleocene record in the Umir Formation. Both a morphological description and a taxonomical and stratigraphical discussion are given for each of the reported species.